Electronic structure and bulk properties of MB6 and MB12 borides: Электpонные свойства металлов и сплавов - Grechnev, G.E.; Baranovskiy, A.E.; Fil, V.D.; Ignatova, T.V.; Kolobov, I.G.; Logosha, A.V.; Shitsevalova, N.Yu.; Filippov, V.B.; Eriksson, Olle (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Ab initio band structure calculations have been carried out for higher boridesMB6 and MB12. High precision measurements of the elastic constants were performed for ZrB12, HoB12, ErB12, TmB12, LuB12, YB6and LaB6 compounds at low temperatures. The bulk properties of the borides have been analyzed on the basisof the calculated equations of states and balanced crystal orbital overlap populations. Our calculations indicatethat hexaborides with divalent metals, CaB6, SrB6, BaB6, and YbB6, are semiconductors with smallenergy gaps. The metallic MB6 hexaborides with trivalent M atoms are found to possess larger bulk modulivalues. For dodecaborides bulk moduli are found to be higher for MB12 with increased filling of the conduction band (ZrB12, HfB12, UB12), comparatively to M3+B12 compounds. The total energy calculations for different magnetic configurations in YbB12 point to a possibility of antiferromagnetic coupling between Yb3+ ions.